SOCIO-POLITICAL PANORAMA IN COSTA RICA (2018): A CITIZEN READING - Herrera Montero, Bernal (2018)
The essay offers a reading of the Costa Rican electoral process of 2018, of its insertion in the national history of the last decades, and of some of the main socio-political rearrangements generated by this process. Some of the factors that defined it are explored: political-party dynamics after the crisis of bipartisanship, the growth of socioeconomic inequality, and the differentiated effects of the incomplete social and economic modernization of the last decades. Partial explanations of the confrontation emerged between a Christian-conser- vative and a secular-modernizing vision, as well as its subsequent evolution. It is proposed that such confrontation, far from revolving around “minor” issues, allowed us to rethink some of the ultimate foundations of national social coexistence.